Study of knowledge and contraception practices in low socio-economic women of Delhi - Pandey, Divya; Garg, Deepali; Salhan, Sudha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective of current study was to assess the knowledge and practice of contraception among the low socio-economic women of reproductive age group in Delhi. Methods: A cross-sectional study was done on 272 low socio-economic women attending a family planning clinic at a Delhi municipal corporation hospital, of which 106 came for Medical Termination of Pregnancy (MTP) and 166 came for family planning advice. They were interrogated through a pre-designed structured questionnaire, to evaluate their knowledge and practices towards regular contraceptive methods, Emergency Contraception (EC) and medical abortion. They were counselled about the available contraceptive methods and allowed to make choices according to their suitability. Results: All women belonged to low socio-economic group according to the modified Kuppuswamy scale. 22.1% were illiterate. 47.8% were ignorant of contraception. 38.3% women were aware of EC. Only 24.2% knew about medical abortion. The main reasons cited for not using contraception was desire for male child (24.6%), fear of side effects (20%), desire for another child (20%), opposition from family members (15.4%), inaccessibility (4.6%) and inconvenience and lack of privacy (5.4%). Conclusions: This study highlights that lack of education, knowledge and awareness led to inadequate usage of regular methods of contraception in reproductive age group women belonging to low socio-economic status. Thus only availability is not sufficient to reach optimum female health. Accessibility need to be increased by educating females and motivating couples to make adequate use of existing family planning methods and resources. In contrast the awareness for emergency contraception is more than regular methods. It mandates need to educate women that emergency contraception should not replace regular methods.